2004
DOI: 10.1074/jbc.m408662200
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Endothelial Cells Regulate Reactive Oxygen Species-induced Cardiomyocyte Apoptosis through Neuregulin-1β/erbB4 Signaling

Abstract: Neuregulin (NRG)-1␤ has a prosurvival effect on cardiac myocytes via the phosphatidylinositol-3-kinase/Akt pathway, but the physiological regulators of this system in the intact heart are unknown. In this study, we tested the hypothesis that reactive oxygen species regulate NRG/erbB signaling. We used isolated adult rat ventricular myocytes (ARVMs) or cardiac microvascular endothelial cells (CMECs) in monoculture, or together in coculture. H 2 O 2 induced NRG-1␤ release from CMECs in a concentration-dependent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
157
0
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 175 publications
(165 citation statements)
references
References 34 publications
5
157
0
3
Order By: Relevance
“…Falls, 2003). The size of released, soluble NRG1 forms found in conditioned media varies considerably depending on the experimental system being used, the domain structure, and glycosylation level and may range from 40 to 80 kDa (Holmes et al, 1992;Ethier et al, 1996;Pollock et al, 1999;Villegas et al, 2000;Wang et al, 2001;Malave et al, 2003;Stove et al, 2003;Kuramochi et al, 2004). The size of the NRG1 isoform that we found in normal cortex-conditioned medium falls within this range.…”
Section: Discussionmentioning
confidence: 52%
“…Falls, 2003). The size of released, soluble NRG1 forms found in conditioned media varies considerably depending on the experimental system being used, the domain structure, and glycosylation level and may range from 40 to 80 kDa (Holmes et al, 1992;Ethier et al, 1996;Pollock et al, 1999;Villegas et al, 2000;Wang et al, 2001;Malave et al, 2003;Stove et al, 2003;Kuramochi et al, 2004). The size of the NRG1 isoform that we found in normal cortex-conditioned medium falls within this range.…”
Section: Discussionmentioning
confidence: 52%
“…Our present findings predict that these mice will show specific impairment in NRG-1β-dependent activation of Src/FAK signaling and FAC formation, particularly under stressed conditions. In preliminary experiments, we have found that the potent activation of NRG-1β/erbB signaling by myocardial ischemia-reperfusion injury [35] is accompanied by phosphorylation of FAK at Y861, and formation of a FAK/erbB2 complex (Kuramochi, Lim and Sawyer, unpublished observation). A morphological analysis of the erbB2 knockout mice during such a stress will help to elucidate the functional significance of the erbB2/Src/FAK pathway.…”
Section: Discussionmentioning
confidence: 98%
“…In proximal renal tubule cells, reoxygenation following hypoxia results in activation of MEK/ERK and PI3K/Akt/XIAP survival signaling pathways, which are mediated through HER1 (20). The anti-apoptotic action of neuregulin 1-β, another member of the EGF-like family, requires phosphorylation of HER-4 in rat hearts exposed to ischemiareperfusion injury (21).…”
Section: Commentmentioning
confidence: 99%